1976
DOI: 10.1121/1.2003396
|View full text |Cite
|
Sign up to set email alerts
|

Generalized theory of the photoacoustic effect

Abstract: The photoacoustic effect is the production of an acoustic signal when a sample in an enclosed cell is illuminated with chopped light. The absorbed light produces a periodic heat flow from the sample to the surrounding gas and backing material, causing pressure variations in the gas which are detected by a sensitive microphone. A theoretical treatment will be presented which involves simultaneous solution of thermal-diffusion equations for the sample and backing material and fluid-dynamic equations for the gas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
4

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 0 publications
0
23
0
4
Order By: Relevance
“…A material prepared by two different methods shows slightly different surface as well as chemical properties. Kuo et al have shown [10] by mirage effect that the thermal diffusivities of differently prepared specimens of SiC differ. In the present paper the effect of method of preparation on thermal diffusivity of Nd 2 O 3 has been determined by photoacoustic technique.…”
Section: Issn: 2348-9812mentioning
confidence: 99%
See 1 more Smart Citation
“…A material prepared by two different methods shows slightly different surface as well as chemical properties. Kuo et al have shown [10] by mirage effect that the thermal diffusivities of differently prepared specimens of SiC differ. In the present paper the effect of method of preparation on thermal diffusivity of Nd 2 O 3 has been determined by photoacoustic technique.…”
Section: Issn: 2348-9812mentioning
confidence: 99%
“…The photoacoustic (PA) effect has been revived as a very useful technique for measuring the optical [1][2][3][4][5][6][7] and thermal [8][9][10] properties of materials because of its high sensitivity and non destructive nature. The basic principle of photoacoustic effect is that a sample illuminated by periodically modulated (chopped) light undergoes optical absorption and gets heated by nonradiative transitions.…”
mentioning
confidence: 99%
“…A disadvantage of this method is that an invasive physical contact is required to accurately measure heat flow through the metallic sample. To overcome this constraint, several groups [9,12,13] have employed the photo-acoustic effect to non-invasively probe metallic phase transformations. In such experiments, phase transition modulates the acoustic signal generated at the surface of a sample when a surrounding ambient gas has been heated by a periodically modulated light beam.…”
Section: Phase-transition Thz Spectroscopy Of Metallic Particlesmentioning
confidence: 99%
“…The product of µ and β is useful in predicting the relationship between the thermal sampling depth and the optical absorption depth [6,7]. If µβ <<1, absorption is unsaturated, the response of the instrument is linear with concentration of the absorbent.…”
Section: The Thermal-acoustic Effectmentioning
confidence: 99%
“…Many theoretical models exist for the thermal-acoustic response of solid and condensed samples have developed theories on the subject [2][3][4][5][6]. Following the derivation of [2], the thermal-acoustic signal (PAS), q, is given by: and ρ is the density, C p is the specific heat, k is the thermal conductivity, β is the optical absorption coefficient, µ is the thermal sampling depth, I o is the incident radiation intensity, γ is the ratio of specific heats, P o is the gas pressure, λ is the length of the cell, T o is the gas temperature, and f is the modulation frequency of the radiation.…”
Section: The Thermal-acoustic Effectmentioning
confidence: 99%